ANALYSIS AND CHARACTERIZATION OF THE INDICATOR ELECTRODE MEMBRANE PVA-ENZYME/GA/PANI-BENZENE SULFONATE ACID/ PVC-KTPCLPB-O-NPOE - Henni Sulastri BR Sinaga; Abd Hakim S (EINSTEIN (e-Journal), 2026)
This research aims to determine the characteristics of indicator electrode membranes using XRD, SEM-EDS and FTIR testing. Differences in the composition of the urease enzyme will affect the diffraction spectrum pattern of the indicator electrode and the use of a conductive polymer, namely PANi, can increase the intensity of the crystal diffraction pattern. The method used is the potentiometric biosensor method with the urease enzyme immobilization technique. The indicator electrode membrane is composed of four layers, namely PVA-enzyme/GA/PANi-Benzene Sulfonic Acid/PVC-KTpClPB-o-NPOE. Based on XRD testing, sample II has the highest intensity of 39170 at 2Î¸ = 24.07°; while sample II has an intensity of 8450 a.u. The resulting diffraction pattern shows that the electrode membrane is a polymeric material as indicated by the presence of crystalline and amorphous patterns. Based on SEM-EDS testing, it shows that the morphological structure of sample I has fewer pores with the tungsten element as the working point, namely 81.98 wt.% and the C element 9.99 wt.% compared to sample II with the tungsten element as the working point. namely 65.60 wt.% and element C 16.41 wt.%. FTIR results show that the transmittance value increases due to the use of polymer in the third layer, namely PANi, so that the best electrode membrane is PVA-Enzyme 1 drop/GA/PANi-Benzene Sulfonic Acid/PVC-KTpClPB-o-NPOE 61% with the highest transmittance in the wave number range 1423.84 cm-1 “ 2914.77 cm-1.